GEM tracker for high-luminosity experiments at the JLab Hall A. Issue 9 (1st September 2016) - Mammoliti, F.; Bellini, V.; Cisbani, E.; Musico, P.; Noto, F.; Perrino, R.; Re, L.; Spinali, S.; Sutera, M. C.; Tortorici, F.; Wojtsekhowski, B.
ABSTRACT: A Large-Acceptance Forward Angle Spectrometer (Super BigBite) is under development for the upcoming experiments in Hall A at Jefferson Lab to optimally exploit the exciting opportunities offered by the 12 GeV upgrade of the electron beam. The tracking of this new apparatus is based on the Gas Electron Multiplier technology, which has been chosen to optimize cost/performance, position resolution and meet the high hits rate (>1 MHz/cm 2 ). In this report we present the technical features of the detector and comment on the presently achieved performance.